The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/08856257.2020.1726091
|View full text |Cite
|
Sign up to set email alerts
|

Social service utilisation in relation to class setting - a longitudinal study among children with mild intellectual disability in Sweden

Abstract: The aim of this study was to investigate if the type of class setting is related to the utilisation of disability-related services and child welfare services outside school over time among children with mild intellectual disability (ID). A quantitative study with a longitudinal and comparative design was carried out including data from archival records concerning service utilisation among 405 children. Children in special classes were more likely than children integrated into regular classes to utilise disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One aspect that appears in this study as a barrier was the inclusion policy that allowed children and adolescents with disabilities to attend mainstream schools, without making adjustments needed for equal participation of all children. In a Swedish study by Olsson et al ( 2020 ) (high-income country) it was found that when children and adolescents with disabilities were integrated into mainstream schools, they were less likely to receive disability-related services from rehabilitation services. The teachers in mainstream schools did not know about available services and could not help the primary caregivers in contacting the concerned authorities.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect that appears in this study as a barrier was the inclusion policy that allowed children and adolescents with disabilities to attend mainstream schools, without making adjustments needed for equal participation of all children. In a Swedish study by Olsson et al ( 2020 ) (high-income country) it was found that when children and adolescents with disabilities were integrated into mainstream schools, they were less likely to receive disability-related services from rehabilitation services. The teachers in mainstream schools did not know about available services and could not help the primary caregivers in contacting the concerned authorities.…”
Section: Discussionmentioning
confidence: 99%
“…There is an online table showing Characteristics (including relevant outcomes such as reading and math scores) of children who maintained or lost access to typical peers (i.e., inclusion throughout (the ages 9–18) and transition from inclusion to special class somewhere between the age of 9 and 18, exact time not reported). The numbers are 26 and 30, thus there are 55 who remained in special education classes not included in the table.McPhillips, 2007 Reason for exclusion Case study of different schools, no effect studyNikolic, 2019 Reason for exclusion Serbia is not a member of OECDNolan, 2020 Reason for exclusion Only schools are analysed, not studentsOcque Karen, 2017 Reason for exclusion compares integrated cotaught (ICT) classrooms and with no ICT classrooms (regular class rooms for students without special needs)Olsson, 2017/09 Reason for exclusion Wrong outcome: The utilisation of habilitation services outside schoolOlsson, 2020/02 Reason for exclusion Wrong outcome: The utilisation of habilitation services outside schoolPandey, 2018/01 Reason for exclusion India is not in the OECDPant, 2016/01 Reason for exclusion India is not in the OECDSalgado, 2001 Reason for exclusion No effects of inclusion for special needs students, comparison is students without disabilitiesSavitz, 2005/03 Reason for exclusion Outcome is not relevant to the present reviewSaylor, 2017/01 Reason for exclusion No students are in special/segregated placementSchulte, 2004/06 Reason for exclusion The purpose of this study was to use school results on a large‐scale, high‐stakes reading test across several years to illustrate the complexities and issues involved in reporting school‐based special education outcomes. Test scores from six elementary schools in one school district in North Carolina were used to examine three different ways of reporting school‐based reading outcomes for students in special education in terms of their ability to provide meaningful, valid information about a school's functioning with students in special education: (a) percentage of students in special education r...…”
Section: Published Notesmentioning
confidence: 99%
“…Palla (Palla, 2019), A. Bloom, S. Critten, H. Johnson, C. Wood (Bloom et al, 2020a, L.M. Olssona, S. Bengtssona, M. Granlunda, K. Huusb, E. Elgmark Andersson and I. Kåreholt (Olssona et al, 2020) in addition to teachers, experts and children themselves, consider it necessary to include parents in the inclusive education process. The researchers may be included as well (Korsgaard et al, 2020: 509).…”
Section: Introductionmentioning
confidence: 99%